2013
DOI: 10.1016/j.jff.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive principles from Cordyceps sinensis: A potent food supplement – A review

Abstract: Extraction Health benefits A B S T R A C T Cordyceps sinensis (CS) is a well-known entamophagus fungus, naturally distributed in the Tibetan Plateau of Asia and Himalayas. Recently this synonym is transferred to Ophiocordyceps by both scientific and non-scientific communities. It is widely used as a tonic and medicinal food in traditional Chinese medicine (TCM), as it possess wonderful health benefits. To support its functional attributes, various investigations have been carried out to find out its adaptogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 112 publications
(114 reference statements)
2
69
0
1
Order By: Relevance
“…However, only 3′-deoxyadenosine (namely, cordycepin), a pharmaceutically active component exhibiting multiple pharmacological actions, was reported to be abundant in CCH. Indeed, cordycepin was originally extracted from C. militaris (Shashidhar et al, 2013), and some studies have shown that large amounts of cordycepin can be found in C. militaris (Guo, Li, Huang, Liang, & Chen, 2006;Wang et al, 2013;Yang, Guan, & Li, 2007), while only trace amounts are present in DCXC, consistent with our current results. Thus, the present result indicated that if the content of cordycepin was abnormally high in the DCXC specimen, adulteration with CCH or C. militaris may have occurred, providing an effective quality control marker.…”
Section: Structural Elucidation Of the Candidate Markersupporting
confidence: 92%
“…However, only 3′-deoxyadenosine (namely, cordycepin), a pharmaceutically active component exhibiting multiple pharmacological actions, was reported to be abundant in CCH. Indeed, cordycepin was originally extracted from C. militaris (Shashidhar et al, 2013), and some studies have shown that large amounts of cordycepin can be found in C. militaris (Guo, Li, Huang, Liang, & Chen, 2006;Wang et al, 2013;Yang, Guan, & Li, 2007), while only trace amounts are present in DCXC, consistent with our current results. Thus, the present result indicated that if the content of cordycepin was abnormally high in the DCXC specimen, adulteration with CCH or C. militaris may have occurred, providing an effective quality control marker.…”
Section: Structural Elucidation Of the Candidate Markersupporting
confidence: 92%
“…[7,8,12,14,15,24,39,48,52,66,67,83,92,98,107,121,136,140,161,162,167,173,177,178,180,188,194,200,207,208,[210][211][212]. [164].…”
Section: 배지 균사체 및 자실체 생산mentioning
confidence: 99%
“…Sung, Hywel-Jones & Spatafora, the most famous and valuable species in the genus of Ophiocordyceps , has been used as herbal medicine in China for centuries. Pharmacological studies on O. sinensis have revealed that the fungus and its fruiting bodies exerted multiple biological and pharmacological effects, such as immunomodulatory, anti-inflammatory, antioxidant, anti-ageing, antitumour, neuroprotective, hepatoprotective and renoprotective effects, and it has been applied to the treatment of kidney, liver and lung disease (Paterson 2008; Shashidhar et al 2013). Chemical studies on the natural fruiting bodies of Ophiocordyceps sinensis (NFOS) have shown the presence of various carbohydrates, nucleosides, cyclodepsipeptides, alkaloids, sterols, fatty acids, amino acids, vitamins, trace minerals and other components (Lo et al 2013; Zhao et al 2014).…”
Section: Introductionmentioning
confidence: 99%